Implementasi Aplikasi Manajemen Arsip Berbasis Website Pada Kantor Notaris Anita Hiramayani Menggunakan Algoritma Rapid Application Development - Atthoriq, Syaifullah; Fauziah, Sifa; Hadikristanto, Wahyu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In an increasingly connected world of information technology, the use of digital solutions to address records management challenges is becoming increasingly important, including in the context of notary offices. Anita Hiramayani Notary Office is one of the leading notary offices operating in Tambun sub-district, the main problem identified is the difficulty of finding data within a certain period of time. Where administrative staff have to spend a long time to track and find the necessary data in piles of various excel files and worksheets. To overcome this problem, Notary Anita Hiramayani's office needs to implement a website-based records management application with the application of the Rapid Application Development algorithm. The results of the research after the implementation of a website-based records management application, show that the application can overcome the problems of records management faced by the notary office can increase efficiency in making reports and the effectiveness of legal services provided by the notary office